2021
DOI: 10.3758/s13415-021-00923-8
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal and Cingulate Thickness Asymmetry Associated with Depressive Symptom Dimensions

Abstract: Both clinical depression and subthreshold depressive symptoms have been associated with alterations in cortical thickness. Studies have yielded conflicting results regarding whether cortical thinning or cortical thickening best characterize the depressive state. Also unclear is whether cortical thickness differences are lateralized. This study examined the relationship between depressive symptom dimensions and cortical thickness asymmetry in cingulate and orbitofrontal regions. Fifty-four community-dwelling ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The posterior cingulate, a key part of the DMN, is a critical hub for self-referential processing, cognitive control and emotion processing, and serves as a cortex underlying multidomain cognitive function through its connections to distal cortical areas ( Li et al, 2022 ). Dotson et al found that patients with StD exhibited reduced cortical thickness in the right posterior cingulate gyrus, compared to the left posterior cingulate gyrus, and this change was associated with more severe somatic symptoms of depression ( Dotson et al, 2021 ). In the present study, we found that the gradient subdivisions of the anterior and posterior cingulate gyrus within the DMN were significantly reduced in patients with StD, and this change was correlated with the severity of depression, which might be an important part of the pathological changes in patients with StD.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior cingulate, a key part of the DMN, is a critical hub for self-referential processing, cognitive control and emotion processing, and serves as a cortex underlying multidomain cognitive function through its connections to distal cortical areas ( Li et al, 2022 ). Dotson et al found that patients with StD exhibited reduced cortical thickness in the right posterior cingulate gyrus, compared to the left posterior cingulate gyrus, and this change was associated with more severe somatic symptoms of depression ( Dotson et al, 2021 ). In the present study, we found that the gradient subdivisions of the anterior and posterior cingulate gyrus within the DMN were significantly reduced in patients with StD, and this change was correlated with the severity of depression, which might be an important part of the pathological changes in patients with StD.…”
Section: Discussionmentioning
confidence: 99%
“…Anticipatory anhedonia correlates with poor social outcomes in depression and can be responsive to connectivity-based transcranial magnetic stimulation treatments ( 48 , 57 ), but may be less responsive to antidepressant treatments. Imaging studies define anhedonia as low reward processing, involving altered cortical thickness ( 58 ) with asymmetry in depressive and subthreshold depressive symptoms.…”
Section: Brain Imaging For Mental Health and Its Relation To Technolo...mentioning
confidence: 99%
“…This study used EEfRT to investigate neural responses of motivation for the self and an unfamiliar other underlying effortful decision-making in individuals with SD. Given that SD has been considered a developmental prodrome to MDD (Dotson et al, 2021;Wesselhoeft et al, 2013), focusing on people with SD could contribute to developing preventive interventions, as well as rule out the effect of clinical treatments (e.g., antidepressant medications) on the motivation and reward processing (He et al, 2019). We focused on neural activity changes in the choice phase between the SD and HC groups as it represents a cost-benefit trade-off between effort costs and potential rewards (Klein-Flügge et al, 2016;Scholl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%